Effect of orange (Citrus sinensis L.) peel essential oil on characteristics of blend films based on chitosan and fish skin gelatin. (June 2021) - Li, Yanjie; Tang, Chunming; He, Qingfeng
Abstract: A novel composite packaging film based on fish ( Cynoglossus semilaevis ) skin gelatin (FSG) and water soluble chitosan (CH) incorporated with the concentrations(0.25, 0.5, 1.0%, v/v) of orange peel essential oils (OPEO) were prepared and characterized. OPEO incorporation dose-dependently lowered the values of tensile strength, elastic modulus, water solubility, moisture content and water vapor permeability. Nevertheless, OPEO raised elongation at break, contact angle. Fourier transform infrared spectroscopy analyses spectra pattern suggested the structural interaction between OPEO and FSG/CH molecules in the films. The noticeable decline in values of L* and a* with coincidental enhancement in values of b*, △E and Opacity were observed when OEPO concentrations increased. Films containing OPEO showed slightly lower degradation temperature and weight loss compared with the control film. Moreover, inclusion of OPEO promoted the inhibitory activity of the bio-composite films against free radicals (DPPH and ABTS) and the tested microorganisms ( Staphylococcus aureus and Escherichia coli ). Overall, it can be suggested that FSG/CH based active blend films incorporated with OPEO could offer potential packaging material to maintain food quality. Graphical abstract: Image 1 Highlights: Developed a novel blend films based on chitosan, fish skin gelatin and OPOE. The physical, mechanical and thermal properties of the films were determined. OPOE improved the barrier properties of the films against light and water. FTIR analysis demonstrated the interaction between OPOE and TSG-Chi. Addition of OPOE increased antioxidant and antibacterial power of the films.